A Bibliometric Analysis of Artificial Intelligence Applications in Spine Care - Zhang, Yu; Hu, Man; Zhao, Wenjie; Liu, Xin; Peng, Qing; Meng, Bo; Yang, Sheng; Feng, Xinmin; Zhang, Liang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background With the rapid development of science and technology, artificial intelligence (AI) has been widely used in the diagnosis and prognosis of various spine diseases. It has been proved that AI has a broad prospect in accurate diagnosis and treatment of spine disorders.Methods On May 7, 2022, the Web of Science (WOS) Core Collection database was used to identify the documents on the application of AI in the field of spine care. HistCite and VOSviewer were used for citation analysis and visualization mapping.Results A total of 693 documents were included in the final analysis. The most prolific authors were Karhade A.V. and Schwab J.H. United States was the most productive country. The leading journal was Spine. The most frequently used keyword was spinal. The most prolific institution was Northwestern University in Illinois, USA. Network visualization map showed that United States was the largest network of international cooperation. The keyword “machine learning” had the strongest total link strengths (TLS) and largest number of occurrences. The latest trends suggest that AI for the diagnosis of spine diseases may receive widespread attention in the future.Conclusions AI has a wide range of application in the field of spine care, and an increasing number of scholars are committed to research on the use of AI in the field of spine care. Bibliometric analysis in the field of AI and spine provides an overall perspective, and the appreciation and research of these influential publications are useful for future research.
Keywords: artificial intelligence; spine; bibliometric; VOSviewer